Biomechanical analysis of the "running" vs. "conventional" diagonal stride uphill techniques as performed by elite cross-country skiers - Pellegrini, B.; Zoppirolli, C.; Stella, F.; Bortolan, L.; Holmberg, H. C.; Schena, F. (Journal of Sport and Health Science, 2022)
Purpose: To compare biomechanical aspects of a novel "running" diagonal stride (DSRUN) with conventional diagonal stride (DSCONV) skiing techniques performed at high speed. Methods: Ten elite Italian male junior cross-country skiers skied on a treadmill at 10 km/h and 10° incline utilizing both variants of the diagonal stride technique. The 3-dimensional kinematics of the body, poles, and roller skis; the force exerted through the poles and foot plantar surfaces; and the angular motion of the leg joints were determined. Results: Compared to DSCONV, DSRUN demonstrated shorter cycle times (1.05 ± 0.05 s vs. 0.75 ± 0.03 s; p < 0.001) due to shorter rolling phase (0.40 ± 0.04 s vs. 0.09 ± 0.04 s; p < 0.001); greater force applied perpendicularly to the roller skis when they had stopped rolling forward (413 ± 190 N vs. 890 ± 170 N; p < 0.001), with peak force being attained earlier; prolonged knee extension, with a greater range of motion during the roller ski-stop phase (28° ± 4° vs.16° ± 3° respectively, p = 0.00014); and more pronounced hip and knee flexion during most of the forward leg swing. The mechanical work performed against friction during rolling was significantly less with DSRUN than with DSCONV (0.04 ± 0.01 J/(m•kg) and0.10 ± 0.02 J/(m•kg) respectively, p < 0.001). Conclusions: Our findings demonstrated that DSRUN is characterized by more rapid propulsion, earlier leg extension, and a greater range of motion of knee joint extension than DSCONV. Further investigations, preferably on snow, should reveal whether DSRUN results in higher acceleration and/or higher peak speed.